Effect of grout strength and block size on the performance of masonry beam. (30th December 2017) - Zohreh Heydariha, Jamshid; Das, Sreekanta; Banting, Bennett
Highlights: This study determined the effect of grout strength, unit size, and construction pattern on masonry beam. The study found that the grout strength has the largest effect on the performance of masonry beam. The study also found that the stack pattern masonry beam performs same way as running bond beam. Ductility indices computed using Priestley and Park's method were found to be conservative. A new method for accurate estimation of the yield displacement and ductility index is presented. Abstract: This study was executed to study the effect of the grout strength and the block unit size on the structural behavior of masonry beams constructed in the traditional running bond and compared with similar masonry beams constructed in stack pattern (stack bond). Full-scale masonry beams, various material, and prism tests were completed under the scope of this study. Various test data using loadcells, strain gauges, displacement gauges, and digital image correlation (DIC) technique were collected and analyzed. The DIC technique was implemented to monitor the crack growth. This study found that the strength of the grout has the largest effect on the structural performance of masonry beam specimens while the effect of the block size is considerable. There is no significant difference in the structural behavior of masonry beam specimens constructed in the stack pattern and running bond. This study also developed and proposed an empirical relationship for accurately determining the yield displacement required for the calculation of the ductility of masonry beam. This empirical relationship is easy-to-use and provides accurate estimation of the ductility index.